A Comparative Study of Optical Properties of Thin Films of MPS-encapsulated CdS Quantum Dots and SiO2/MPS-encapsulated CdS Quantum Dots Mixture - Koc, Kenan (PLEIADES PUBLISHING LTD, 2019)
The aim of this study is to investigate the optical properties of thin films of MPS-encapsulated CdS quantum dots (QDs) and SiO2/MPS-encapsulated CdS QDs mixture. For this purpose, SiO2 sol and colloidal MPS-encapsulated CdS QDs were mixed and then deposited on a glass substrate by spin coating. Also, the spin coating method was used to deposit the colloid-produced MPS-encapsulated CdS QDs and in this way the QDs were self-assembled onto the glass substrate. The films were heat treated at 150 degrees C under N-2 atmosphere. The optical properties of the films were characterized by UV-Vis absorption spectrophotometer and NKD spectrophotometer measurements. The refractive index and thickness of the films were calculated by fitting the measured data in a Drude-Lorentz model. The refractive index values were found 1.90 and 1.51 for the thin films of the MPS-encapsulated CdS QDs and SiO2/QDs mixtures, respectively. According to this result, the refractive index value of the SiO2/CdS QDs mixture thin film is close to the glass substrate and such films may be a good candidate for planar luminous solar concentrators.
Keywords: optical properties; quantum dots; thin films; STRUCTURAL-PROPERTIES; SIZE; Optics; Spectroscopy